Authorization and Toxicity of Veterinary Drugs and Plant Protection Products: Residues of the Active Ingredients in Food and Feed and Toxicity Problems Related to Adjuvants - Klátyik, Szandra; Bohus, Péter; Darvas, Béla; Székács, András (Frontiers in Veterinary Science, 2017)
Chemical substances applied in animal husbandry or veterinary medicine and in crop protection represent substantial environmental loads, and their residues occur in food and feed products. Product approval is governed differently in these two sectors in the European Union (EU), and the occurrence of veterinary drug and pesticide residues indicated by contamination notification cases in the Rapid Alert System for Food and Feed of the EU also show characteristic differences. While the initial high numbers of veterinary drug residues reported in 2002 were successfully suppressed to less than 100 cases annually by 2006 and on, the number of notification cases for pesticide residues showed a gradual increase from a low (approximately 50 cases annually) initial level until 2005 to more than 250 cases annually after 2009, with a halt occurring only in 2016. Main notifiers of veterinary drug residues include Germany, Belgium, the United Kingdom and Italy (63, 59, 42 and 31 notifications announced, respectively) and main consigning countries of non-compliances are Vietnam, India, China and Brazil (88, 50, 34 and 23 notifications, respectively). Thus, countries of South and Southeast Asia are considered a vulnerable point with regards to veterinary drug residues entering the EU market. Unintended side-effects of veterinary drugs and plant protection products may be caused not only by the active ingredients, but also by various additives in these preparations. Adjuvants (e.g., surfactants) and other co-formulants used in therapeutic agents and feed additives, as well as in pesticide formulations have long been considered as inactive ingredients in the aspects of the required main biological effect of the pharmaceutical or pesticide, and in turn, legal regulations of the approval and marketing of these additives specified significantly less stringent risk assessment requirements, than those specified for the active ingredients. However, numerous studies have shown additive, synergistic or antagonistic side-effects between the active ingredients and their additives in formulated products, moreover, toxicity has been evidenced for various additives. Therefore, toxicological evaluation of surfactants and other additives is essential for proper environmental risk assessment of formulations used in agriculture including animal husbandry and plant protection.